Neuroanatomical abnormalities before onset of delusions in patients with Alzheimer’s disease: a voxel-based morphometry study - Nakaaki, Shutaro (Dove Medical Press, 2013)
BACKGROUND: Structural brain abnormalities associated with delusions in Alzheimer’s disease are poorly understood. In addition, whether the neural substrate underlying the delusions develops before the onset of the delusions is unclear. In this study, we used a voxel-based morphometry approach to examine the existence of regional structural abnormalities at baseline in patients with Alzheimer’s disease who did and who did not develop delusions. METHODS: Using the Neuropsychiatric Inventory, we identified patients with Alzheimer’s disease who exhibited delusions during a 2-year period. All the patients had undergone a magnetic resonance imaging examination at the start of the study period (baseline). We conducted a voxel-based morphometry analysis using statistical parametric mapping (SPM5) software and compared the results of patients with Alzheimer’s disease who did and did not develop delusions. RESULTS: Compared with the patients who did not develop delusions (n = 35), the patients who did develop delusions (n = 18) had significantly smaller gray matter volumes on both sides of the parahippocampal gyrus, the right posterior cingulate gyrus, the right orbitofrontal cortex, both sides of the inferior frontal cortex, the right anterior cingulate, and the left insula. CONCLUSION: Structural brain abnormalities involving both the frontal and medial temporal lobes may be crucial to the expression of delusions in patients with Alzheimer’s disease.